Agha Musa Naghiev Karbala’i—The Man and His Multiple Identities: Between National-Azerbaijani, Shi‘i Muslim, and Bahá’í Religious Identities - Shahṿar, Soli (Religions, 2023)
Aqa Musa Naghiev Karbala’i (1849–1919)—an oil magnate from Baku and a significant figure in the modern history of Baku and Azerbaijan—and his multiple identities are the focus of this article. Alongside his National-Azerbaijani identity, Naghiev’s religious identity was divided between the Shi‘i Muslim and Bahá’í identities. The circumstances in which Naghiev was born and raised, and lived, especially during his adulthood—as a Shi‘i who had converted to the Baha’i faith, living among the majority Shi‘i Muslim population who were generally alien to Baha’is—dictated, at times, the need to carefully maneuver between these two religious identities. The Baha’i principle of hikmat provided Naghiev with the appropriate means for this during his lifetime. The problem, however, is in the way his identity has been engineered and presented in Azerbaijan’s national historical consciousness as an Azerbaijani-Muslim, concealing his Baha’i religious identity, in spite of his public activities for Baha’is and the Baha’i community, which included financing the building of the Baha’i Spiritual Assembly in Baku (Ruhanie) and being the chairman of its management committee. In this article, I explain this complex picture of Naghiev’s multiple identities through the use of primary (documents from national and private archives, and interviews) and secondary sources.